2019
DOI: 10.1002/aur.2061
|View full text |Cite
|
Sign up to set email alerts
|

The role of alexithymia in parent–child interaction and in the emotional ability of children with autism spectrum disorder

Abstract: Children with autism spectrum disorder (ASD) have more emotional difficulties than typically developing (TD) children. Of all the factors that impact children's emotional development, parents, and the way they interact with their children, are of crucial importance. The present study compared the amount of parent–child interactions among 35 dyads of parents and their children with ASD and 41 dyads of parents and their TD children, aged between 3 and 13 years, during a frustration‐eliciting situation. We furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…A recent study found a relationship between children’s alexithymia and a reduction in parent–child interactions in the presence of a diagnosis of ASD, when compared to parents of typically developed children ( Costa et al, 2019 ). Moreover, a 2019 review have revealed that parental verbal responsiveness to their children’s focus of attention predicted children’s expressive and receptive language ( Edmunds et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found a relationship between children’s alexithymia and a reduction in parent–child interactions in the presence of a diagnosis of ASD, when compared to parents of typically developed children ( Costa et al, 2019 ). Moreover, a 2019 review have revealed that parental verbal responsiveness to their children’s focus of attention predicted children’s expressive and receptive language ( Edmunds et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that alexithymia in children with ASD was associated with less expressive coherence (Costa et al, 2017), empathy, and perspective taking (Lartseva et al, 2015) as well as lower enjoyment of prosocial interactions (Gebauer et al, 2014). Moreover, as highlighted by Costa et al (2019), alexithymia in children (more than ASD status) can negatively affect parent-child relationships, explaining the reduced amount of dyadic exchanges. The mismatch between arousal activation and subjective experience of feelings (Gaigg et al, 2018) may also contribute to the formation of less coherent child representation influencing how information is encoded and processed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a substantial lack of research concerning the association between alexithymia and attachment in children with ASD. A recent study (Costa et al, 2019) found that alexithymia predicts reduced parent-child interaction more than ASD status, suggesting the need to consider its impact on quality of relationship in future research. In fact, the study did not include a specific measure of attachment relationship to parents, which represents a core feature of child socioemotional development.…”
Section: Attachment and Alexithymia In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…Costa et al (2017) coded valence of facial expressions and behaviors in 10-s intervals during a toy-removal task and reported more negative behaviors and more negative facial expressions in school-aged children with ASD compared to typically developing peers. Another more recent study by Costa et al (2019) examined ER (frequency of negative, neutral, and positive facial expressions) in children (aged 3–13 years) with and without ASD during a toy-removal task with their parent and found a higher frequency of negative and neutral, and lower frequency of positive, facial expressions among ASD youth. Taken together, this research generally suggests increased negativity in response to frustration in ASD youth, but also points to the importance of considering multiple methods for quantifying negative response in order to better understand what this increased negativity looks like.…”
Section: Negative Er In Individuals With Asdmentioning
confidence: 99%